2017
DOI: 10.1111/ggi.13224
|View full text |Cite
|
Sign up to set email alerts
|

Balloon pulmonary angioplasty is effective for treating peripheral‐type chronic thromboembolic pulmonary hypertension in elderly patients

Abstract: BPA is an effective treatment for peripheral-type CTEPH regardless of age; however, higher age, N-terminal pro-brain natriuretic peptide values before treatment and an underlying psychiatric disorder might be associated with minor complications. Geriatr Gerontol Int 2018; 18: 678-684.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…1). Of these, 11 studies presented outcomes for 755 patients with inoperable CTEPH treated with BPA (Table 1) 8,[22][23][24][25][26][27][28][29][30][31] . Twenty-three studies reported outcomes in 849 patients with inoperable CTEPH treated with pulmonary vasodilators (Table 1) 10-12,32-51 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Of these, 11 studies presented outcomes for 755 patients with inoperable CTEPH treated with BPA (Table 1) 8,[22][23][24][25][26][27][28][29][30][31] . Twenty-three studies reported outcomes in 849 patients with inoperable CTEPH treated with pulmonary vasodilators (Table 1) 10-12,32-51 .…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with our results. However, Phan et al 's investigation did not include several key studies pertaining to BPA 8,[22][23][24][25][26][27][28][29] and pulmonary vasodilators 12,33,34,39,43,46 . Wang et al also compared riociguat to BPA in patients with inoperable CTEPH 58 .…”
Section: Discussionmentioning
confidence: 99%
“…However, that study included only 31 patients and chose a relatively young age for identifying elderly patients (65 years). Two more recent studies in elderly patients have confirmed the effectiveness of BPA, although they included only 10 patients aged ≥75 years ( 9 ) and eight patients aged ≥70 years ( 10 ). A French study that compared BPA and PEA results in patients aged ≥80 years also showed good results in the 21 patients who underwent BPA ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…BPA is a promising treatment for peripheral-type CTEPH and inoperable CTEPH patients, with a better prognosis regardless of age. 12 , 18 Furthermore, several reports have shown that BPA improves QoL. Darocha et al reported that baseline QoL in patients with CTEPH was significantly worse than in the healthy population and, after a series of BPA procedures, QoL improved significantly on all scales, as well as on scales normalized relative to the healthy population, except for pain experience.…”
Section: Discussionmentioning
confidence: 99%
“…11 Patients were considered to have a psychiatric disorder if they had been diagnosed by psychiatrists or had taken antipsychotic agents. 12 …”
Section: Methodsmentioning
confidence: 99%